Dietary guidelines for prevention and management of obesity, diabetes and hypertension - Zephirin, Manuelita, ed. (CFNI KingstonJM, 1986)
Lists strategies for prevention and control of metabolic diseases viz. daibetes, hypertension, obesity. Appendicies contain height and weight table for women and men, weight for height of boys aged 5-11 years, and weight for height of girls aged 5-10 years.